Analisis faktor yang memengaruhi produksi ASI pada ibu melahirkan sectio caesar dan normal - Cahayani, Julia Annisa; Amalia, Linda; Suparto, Tirta Adikusuma (Holistik Jurnal Kesehatan, 2025)
Background: Breastfeeding is a fundamental aspect of maternal and infant health, playing a crucial role in preventing stunting and supporting optimal child development. Even though the primary dietary source during the first half-year of life, infants should receive only breast milk to meet their nutritional needs, various factors can affect its production. One such factor is the mode of delivery, where mothers who undergo cesarean section tend to face more breastfeeding challenges compared to those with vaginal delivery. In addition, nutritional intake, psychological condition, rest patterns, and breastfeeding frequency also significantly influence successful lactation. Understanding these factors is essential to support effective interventions for improving breastfeeding outcomes. Purpose: To analyze the factors that influence breast milk production in mothers who give birth by caesarean section and normal delivery. Method: This study used a quantitative approach with a cross-sectional design. The research sample was 134 breastfeeding mothers with babies aged 0-1 months in the Jonggol Health Center working area, using quota sampling (67 mothers gave birth normally and 67 mothers gave birth by caesarean section). Data collection was carried out through questionnaires and analyzed using the chi-square test. Results: There was a substantial correlation between moms' breast milk output and their dietary consumption who had vaginal deliveries (p = 0.008) and those who underwent cesarean sections (p = 0.027). Psychological condition was also significantly associated with breast milk production in both vaginal delivery (p = 0.036) and cesarean section groups (p = 0.016). Similarly, rest patterns showed a significant relationship with the production of breast milk during cesarean sections (p = 0.003) and vaginal deliveries (p = 0.015). Furthermore, in both vaginal delivery (p = 0.003) and cesarean surgery (p = 0.021), a high link between the frequency of nursing and the supply of breast milk was found. Additionally, there was a strong correlation between the technique of delivery and the production of breast milk (p = 0.035), with mothers who delivered vaginally tending to have more adequate and smoother milk production compared to those who had cesarean sections Conclusion: Nutritional intake, psychological condition, rest patterns, breastfeeding frequency, and mode of delivery were significantly associated with breast milk production. Mothers with vaginal delivery and supportive lifestyle factors were more likely to experience optimal lactation.   Keywords: Breast Milk Production; Breastfeeding Mothers; Cesarean Section; Vaginal Delivery.   Pendahuluan: Pemberian ASI merupakan aspek mendasar dari kesehatan ibu dan anak, yang berperan penting dalam mencegah terhambatnya pertumbuhan dan memastikan tumbuh kembang anak yang optimal. Meskipun Selama enam bulan pertama kehidupan bayi, ASI disarankan sebagai makanan utama mereka, beberapa faktor dapat memengaruhi kelancaran produksi ASI. Salah satunya adalah jenis persalinan, karena Ibu yang menjalani persalinan secara sectio caesarea memiliki kecenderungan tingkat kesulitan menyusui yang lebih besar dibandingkan ibu dengan persalinan normal. Selain itu, pola menyusui, status psikologis, pola tidur, dan frekuensi menyusui juga memengaruhi keberhasilan produksi ASI. Memahami faktor-faktor tersebut diperlukan untuk mendukung intervensi yang tepat guna meningkatkan kualitas pemberian ASI. Tujuan: Untuk menganalisis faktor yang memengaruhi produksi ASI pada ibu melahirkan sectio caesar dan normal. Metode: Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Sampel terdiri dari 134 ibu menyusui dengan bayi usia 0-1 bulan di wilayah kerja Puskesmas Jonggol, menggunakan quota sampling (67 ibu melahirkan normal dan 67 ibu sectio caesarea). Data dikumpulkan melalui kuesioner dan dianalisis dengan uji chi-square. Hasil: Terdapat hubungan yang signifikan antara pola makan dan produksi ASI pada persalinan normal (p = 0.008) dan sectio caesarea (p = 0.027). Terdapat hubungan signifikan terhadap psikologis dan produksi ASI pada persalinan normal (p = 0.036) dan sectio caesarea (p = 0.016). Terdapat hubungan signifikan pola istirahat dan produksi ASI pada persalinan normal (p = 0.015) dan sectio caesarea (p = 0.003). Terdapat hubungan signifikan terhadap frekuensi menyusui dan produksi ASI pada persalinan normal (p = 0.003) dan sectio caesarea (p = 0.021). Selain itu, terdapat hubungan yang signifikan antara jenis persalinan terhadap produksi ASI dengan nilai     p = 0.035 (p < 0.05). Ibu yang melahirkan secara normal cenderung memiliki produksi ASI yang lebih lancar dibandingkan ibu yang melahirkan secara sectio caesarea. Simpulan: Pola makan, psikologis, pola istirahat, frekuensi menyusui, dan jenis persalinan memiliki hubungan yang signifikan terhadap kelancaran produksi ASI. Ibu yang melahirkan secara normal, memiliki pola makan baik, kondisi psikologis stabil, istirahat cukup, dan frekuensi menyusui tinggi, cenderung memiliki produksi ASI yang lebih lancar.   Kata Kunci: Ibu Menyusui; Persalinan Normal; Produksi ASI; Sectio Caesarea.